XBRL Adoption and Information Asymmetry : Evidence from the Indian Capital Market - Gupta, Sushant; Chandel, Ajay; Bhalla, Lalit (Indian Journal of Finance, 2023)
Purpose : The study was conducted in the context of the Indian capital market to find out the effect of adopting XBRL (eXtensible Business Reporting Language) on the reduction of information asymmetry and the impact of XBRL on the trading volume of the market. Methodology : In the current study, trading volume has been taken as the proxy variable to study the impact of XBRL adoption on information asymmetry. The study focused on the pre-and postadoption XBRL effect on information asymmetry, followed by the influence of the implementation of XBRL, which is measured by taking the trading volume of the Indian capital market as a proxy variable. Data for 270 listed firms were collected for this research during a 20-year period, from 2001–2020, including 11 years before the implementation of XBRL and 9 years after it. Findings : There is a significant difference in the information asymmetry pre- and post-adoption of XBRL by Indian listed firms. A strong positive and significant relationship has been found between XBRL and the trading volume of the Indian capital market due to a reduction in information asymmetry. Practical Implications : Listed companies might increase investments by offering their stakeholders XBRL-enabled software and services. Regulatory authorities can also enable companies to disclose reports that are useful to decision-making stakeholders according to the XBRL taxonomy. The adoption of XBRL helps reduce information asymmetry, increase companies’ valuation, and lower the cost of capital. Originality : This study contributes to the financial reporting and Indian capital markets fields. This study contributes to the literature by identifying the impact on Indian capital markets post-adoption of XBRL.